A secondary Research on Medicinal Plants Mentioned in the Holy Qur'an - Md. Sanower Hossain; Zannat Urbi; Fatematuz Zuhura Evamoni; Fatama Tous Zohora; K. M. Hafizur Rahman (Institue of Medicinal Plants, ACECR, 2016)
Background: Finding scientific data from the Holy Qur'an is an old trend, which emerge newly with rise of modern science. In the literature, we have found that total number of medicinal plants cited in the Holy Qur'an varies author to author. Objective: The aim of this study was to indentify the plants mentioned in the Holy Qur'an and to confirm the botanical name with other relevant information and Islamic history of medicine. Methods: The Holy Qur'an has been studied thoroughly to identify the medicinal plants, and Surah and verses were only chosen if they stated specific name of plants which are found in the earth. The identity of the selected plants was confirmed and claim of ethnomedicinal uses of Qur'anic medicinal plants was vindicated using scientific evidence available in the journals and books. Results: Our present findings revealed a total of 27 plants cited in 47 verses of 28 Surah in the Holy Qur'an, those belongs to 22 genera of 18 families of plant kingdom. Among these plants, eight fruits, five vegetables, two crops, six aromatics, five trees and one forage species. Out of 27, 15 plants have been consumed in raw form or in cuisine which directly contribute nutrition to our body as well as medicinal benefits. Conclusion: It is concluded that identified medicinal plants extensively used in the traditional healing system due to their availability, acceptability, compatibility and affordability and studied in modern science for identifying theory of their potential role in improving the quality of life.